Beyond T2 and 3T: New MRI techniques for clinicians. (September 2019) - Knowles, Benjamin R.; Friedrich, Florian; Fischer, Carola; Paech, Daniel; Ladd, Mark E.
Highlights: This review paper covers topics regarding new clinical techniques in MRI that can aid clinicians in diagnosis and treatment response of tumors, as well and guidance during therapy. New MRI techniques in radiotherapy. Ultrahigh field MRI. Non proton and metabolism imaging. Abstract: Technological advances in Magnetic Resonance Imaging (MRI) in terms of field strength and hybrid MR systems have led to improvements in tumor imaging in terms of anatomy and functionality. This review paper discusses the applications of such advances in the field of radiation oncology with regards to treatment planning, therapy guidance and monitoring tumor response and predicting outcome.